Oxygen Variability During ENSO in the Tropical South Eastern Pacific - Espinoza-Morriberón, Dante; Echevin, Vincent; Colas, Francois; Tam, Jorge; Gutierrez, Dimitri; Graco, Michelle; Ledesma, Jesús; Quispe-Ccalluari, Carlos (Frontiers in Marine Science, 2019)
The Oxygen Minimum Zone (OMZ) of the Tropical South Eastern Pacific (TSEP) is one of the most intensely deoxygenated water masses of the global ocean. It is strongly affected at interannual time scales by El Niño (EN) and La Niña (LN) due to its proximity to the equatorial Pacific. In this work, the physical and biogeochemical processes associated with the subsurface oxygen variability during EN and LN in the period 1958 – 2008 were studied using a regional coupled physical-biogeochemical model and in situ observations. The passage of intense remotely forced coastal trapped waves caused a strong deepening (shoaling) of the OMZ upper limit during EN (LN). A close correlation between the OMZ upper limit and thermocline depths was found close to the coast, highlighting the role of physical processes. The subsurface waters over the shelf and slope off central Peru had different origins depending on ENSO conditions. Offshore of the upwelling region (near 88°W), negative and positive oxygen subsurface anomalies were caused by Equatorial zonal circulation changes during LN and EN, respectively. The altered properties were then transported to the shelf and slope (above 200 m) by the Peru-Chile undercurrent. The source of nearshore oxygenated waters was located at 3°S – 4°S during neutral periods, further north (1°S – 1°N) during EN and further south (4°S – 5°S) during LN. The offshore deeper (< 200 – 300 m) OMZ was ventilated by waters originating from ~ 8°S during EN and LN. Enhanced mesoscale variability during EN also impacted OMZ ventilation through horizontal and vertical eddy fluxes. The vertical eddy flux decreased due to the reduced vertical gradient of oxygen in the surface layer, whereas horizontal eddy fluxes injected more oxygen into the OMZ through its meridional boundaries. In subsurface layers, remineralization of organic matter, the main biogeochemical sink of oxygen, was higher during EN than during LN due to oxygenation of the surface layer and in spite of a reduced primary production. Sensitivity experiments highlighted the larger impact of equatorial remote forcing with respect to local wind forcing during EN and LN.